TUBERCULOSIS AND IRON-CONTAINING CHEMOTHERAPY DRUGS - Rakhmonova Kamola Muzrobovna (Zeta Repository, 2023)
Today in our country, special attention is paid to improving the health care system, including early diagnosis, treatment and prevention of tuberculosis. Some features of iron metabolism in mycobacteria are considered, as well as varieties and pathogenesis of various variants of anemia that can develop in tuberculosis: iron deficiency (subcutaneous iron deficiency), associated with chronic disease (with relative iron deficiency) or medicinal (variants: sideroachrestic, hemolytic, aplastic). The possibilities of correcting tuberculosis treatment regimens by introducing a complex compound of iron with isoniazid in order to reduce undesirable adverse reactions to isoniazid are analyzed.